INTERPERSONAL COMMUNICATION IN CHILDREN OF PRIMARY SCHOOL AGE - Svetlana TOLSTAIA; Maria ROȘCA (Universitaria Publishing House, Craiova, 2022)
In contemporary society, communication is a subject of certain topicality and of particular importance in the process of development and formation of every human being. Communication helps young pupils to engage in dialogue, ask questions and receive responses, communicate assertively with adults, communicate positively with peers, accept the opinions of peers and adults, identify the right time to initiate a dialogue with adults or peers, to conclude a dialogue in a fair and polite manner. Communication efficiency, however, depends on the level of development of the communication skills of the communicators. The development of interpersonal communication skills begins early, having its specificity at each age. The development of communication skills is a process of great complexity and especially the primary school age it coincides with the social integration of the child in an organized group where communication has a very important role for establishing the relationship with others. Interpersonal relationships are established and evolve based on the background of interpersonal communication between people, treating them as conscious and direct psychological alliances between people. Interpersonal relationships of primary school children are formed and developed based on individual particularities, as well as based on the types of relationships internalized and learned from the family and the school environment. In the present study we have to analyze the ability of young school pupils to communicate effectively.